P Wave Indices—Advancing Our Understanding of Atrial Fibrillation-Related Cardiovascular Outcomes - Chen, Lin Y.; Soliman, Elsayed Z. (Frontiers in Cardiovascular Medicine, 2019)
Atrial fibrillation (AF) is associated with an increased risk of ischemic stroke, heart failure, cognitive decline, dementia, myocardial infarction, sudden cardiac death, and all-cause death. Although these associations are firmly established, our understanding of the underlying mechanisms remains incomplete. Accumulating evidence suggests that left atrial (LA) abnormality or atrial cardiomyopathy may explain the relationship of AF to the aforementioned outcomes. P-wave indices (PWIs) reflect underlying atrial remodeling. In this mini review, we define representative PWIs, discuss state-of-the-art knowledge on the relationship between abnormal PWIs and AF-related cardiovascular outcomes (focusing on ischemic stroke and sudden cardiac death), and propose directions for future research. Our ultimate goal is to present a practical way forward to advance the emerging field of LA abnormality or atrial cardiomyopathy.